2022
DOI: 10.1186/s12889-022-13966-4
|View full text |Cite
|
Sign up to set email alerts
|

Six-year prognosis of anxiety and depression caseness and their comorbidity in a prospective population-based adult sample

Abstract: Background Anxiety and depression are amongst the most prevalent mental health problems. Their pattern of comorbidity may inform about their etiology and effective treatment, but such research is sparse. Here, we document long-term prognosis of affective caseness (high probability of being a clinical case) of anxiety and depression, their comorbidity, and a no-caseness condition at three time-points across six years, and identify the most common prognoses of these four conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Further, the current study found that participants experiencing symptoms of depression and anxiety were more likely to report higher mean scores on each barrier than those experiencing anxiety symptoms alone. This is the first study to report these findings in the perinatal sample, which is consistent with the literature demonstrating that those with higher levels of co-morbidity have poorer mental health treatment outcomes in the general population (Gaspersz et al ., 2018; Stålner et al ., 2022). These findings may have implications for the delivery of treatment, with those mothers experiencing depression and anxiety symptoms potentially requiring additional assistance to overcome treatment barriers and greater support during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the current study found that participants experiencing symptoms of depression and anxiety were more likely to report higher mean scores on each barrier than those experiencing anxiety symptoms alone. This is the first study to report these findings in the perinatal sample, which is consistent with the literature demonstrating that those with higher levels of co-morbidity have poorer mental health treatment outcomes in the general population (Gaspersz et al ., 2018; Stålner et al ., 2022). These findings may have implications for the delivery of treatment, with those mothers experiencing depression and anxiety symptoms potentially requiring additional assistance to overcome treatment barriers and greater support during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…2 11 Depressed mood, therefore, impairs the achievement of functional and personal goals of those affected, negatively affecting their HRQoL. 4 Lastly, comorbid depressed mood predicts severe morbidity, substance misuse and treatment resistance. 2 4 5 Given the multilevel effects of depressed mood, especially if allowed to progress, early detection, referral and management are critical.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%